P01.062 Probability maps of glioblastoma indicate variation in surgical decisions between twelve surgical teams. (19th September 2018) - Müller, D; Robe, P; van den Brink, W; Ardon, H; Idema, B; Kloet, F; Wagemakers, M; Barkhof, F; Vandertop, P; Bello, L; Conti Nibali, M; Rossi, M; et al.
Abstract: Background: The aim of glioblastoma surgery is to maximize the extent of resection, while preserving functional integrity. Standards are lacking for surgical decision-making and consequently surgical strategies may differ between neurosurgical teams. In this study we quantitated and compared surgical decision-making throughout the brain between neurosurgical teams for patients with a glioblastoma using probability maps. Material and Methods: All adults with first-time glioblastoma surgery in 2012–2013 from twelve tertiary referral centers for neuro-oncological care were included in this study. For each patient, pre- and postoperative tumor were manually segmented on MRI and aligned to standard brain space. Resection probability maps and biopsy probability maps were constructed in 1 mm resolution for each team's cohort. Brain regions with differential biopsy and resection results between teams were identified. Results: The study cohort consisted of 1085 patients of whom 305 received a biopsy and 780 a resection. Biopsy probability maps demonstrated differences between teams in biopsy rate per brain location, such as for the right caudate nucleus, indicating variation in biopsy decisions. Resection probability maps demonstrated differences between teams in residual tumor rate per brain location, such as for the left sagittal striatum and neighboring posterior corpus callosum, indicating variation in resection decisions. Conclusion: Biopsy and resection probability maps indicate treatment variation between teams for patients with a glioblastoma. This conveys useful objective arguments for quality of care discussions between surgical teams for these patients.